Rap, racism, and visibility: black music as a mediator of young Israeli-Ethiopians' experience of being 'Black' in a 'White' society. Issue 1 (2nd January 2019) - Ratner, David
ABSTRACT: In the mid-1990s, descriptions of a new topic began to appear in Israeli media as well as in academic writing, of Israeli-Ethiopian youngsters who identified with black music in general and rap/hip-hop in particular. In this paper, I challenge previous interpretations for this phenomenon, arguing that they were insufficiently based on meanings that the youngsters themselves attach to their musical preferences. The study is based on semi-structured in-depth interviews with 40 young Israeli-Ethiopian men. The interviews were focused on meanings young Israeli-Ethiopians attach to rap music, which is their favorite musical style. The study shows that the pivotal experience which associates them with black music and is central to their identity in general is their constant visibility through the white-Israeli people's gaze. This visibility, reflected in constant reminders by the 'white' Israeli society of the Ethiopian adolescents being 'black', makes the adolescents fascinated by black music and rap music in particular, which they perceive to be offering them a resonance of their experiences, comfort, and empowerment. Black music in general, and rap music in particular, resonates with the lived experiences of Black Ethiopian Israelis and it serves as a symbolic bridge through which the youngsters connect to the historical narratives of the African trans-Atlantic diaspora, and draw inspiration from them.